Prion induction involves an ancient system for the sequestration of aggregated proteins and heritable changes in prion fragmentation - Tyedmers, Jens; Treusch, Sebastian; Dong, Jijun; McCaffery, J. Michael; Bevis, Brooke; Lindquist, Susan (Proceedings of the National Academy of Sciences of the United States of America, 2010)
When the translation termination factor Sup35 adopts the prion state, [PSI+], the read-through of stop codons increases, uncovering hidden genetic variation and giving rise to new, often beneficial, phenotypes. Evidence suggests that prion induction involves a process of maturation, but this has never been studied in detail. To do so, we used a visually tractable prion model consisting of the Sup35 prion domain fused to GFP (PrD-GFP) and overexpressed it to achieve induction in many cells simultaneously. PrD-GFP first assembled into Rings as previously described. Rings propagated for many generations before the protein transitioned into a Dot structure. Dots transmitted the [PSI+] phenotype through mating and meiosis, but Rings did not. Surprisingly, the underlying amyloid conformation of PrD-GFP was identical in Rings and Dots. However, by electron microscopy, Rings consisted of very long uninterrupted bundles of fibers, whereas Dot fibers were highly fragmented. Both forms were deposited at the IPOD, a biologically ancient compartment for the deposition of irreversibly aggregated proteins that we propose is the site of de novo prion induction. We find that oxidatively damaged proteins are also localized there, helping to explain how proteotoxic stresses increase the rate of prion induction. Curing PrD-GFP prions, by inhibiting Hsp104’s fragmentation activity, reversed the induction process: Dot cells produced Rings before PrD-GFP reverted to the soluble state. Thus, formation of the genetically transmissible prion state is a two-step process that involves an ancient system for the asymmetric inheritance of damaged proteins and heritable changes in the extent of prion fragmentation.
Gesehen am 26.01.2024